Transforming literacy experiences into child's play - Diaz, Leonor E. (2004)
This paper leads the reader to understand the relationship and value of linking literacy and play activities for young learners. Teachers will be able to find gems of insights and teaching ideas in this article. Through a study both theory and practical experience, the author is able to bring forward teaching suggestions that will surely be useful for classroom teachers.
Keywords: Early childhood education; Teaching methods -- Research